Membaca Pemikiran Kuntowijoyo dalam Hubungan Ilmu dan Agama Perspektif Islam - Siti Qurrotul A'yuni; Radia Hijrawan (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
This study examines the thoughts of Kuntowijoyo as a Muslim scholar who is very influential in Indonesian scientific disciplines. In his view, Indonesian Muslims have gone through stages of awareness. These stages are divided into three periods, namely: the period of myth, the period of ideology and the period of science.The mythical period where ancient people really believed in something mystical. Then the development of the era in the Ideological Period began to recognize scientific treasures so that some of these mystical beliefs could be proven by science. Meanwhile, humans are currently in the Period of Science, namely interpreting modern sciences. A detailed explanation related to the period was compiled based on several references obtained by the author in qualitative research methods and packaged in the Library Research. The author identifies through Kuntowijoyo's original work and explores other scientific studies related to his written thoughts, both in print and digital media. The results show the study of Islam as a science, the method of transcendental structuralism and the concept of prophetic social science according to Kuntowijoyo in an Islamic perspective.